Psychometrical analysis of Lodahl and Kejner’s Job Involvement Scale in workers from Arequipa - Arias Gallegos, Walter L. (2017)
In the following article we present a psychometric analysis of Lodahl and Kejner’s Job Involvement Scale, which contains 20 items in a Likert scale with five alternatives to answer. This instrument has seven factors and adequate levels of validity and reliability according to the classic theory of tests. We applied the test to 223 workers at Arequipa City, from the health and administrative occupational field. The results indicate that the test have adequate homogeneity and an internal structure of five factors: absorption for work, irrelevance of work, concern for work, sense of work and unmotivation. Its levels of reliability are located over 0.725, obtained by the Cronbach’s Alpha Test. We conclude the test is valid and reliable.